Combined puncture/cutting of elastomer membranes by pointed blades: Characterization of mechanisms. Issue 26 (21st March 2015) - Triki, Ennouri; Nguyen‐Tri, Phuong; Gauvin, Chantal; Azaiez, Meriam; Vu‐Khanh, Toan
ABSTRACT The simultaneous puncture and cutting behavior of elastomers was investigated by pointed blades. Puncture/cutting tests by three‐pointed blades were performed with different elastomer membranes, including butyl, neoprene, and nitrile rubbers. The fracture mechanisms associated to puncture/cutting were investigated. The quantitative material properties which control the puncture/cutting resistance are obtained. The results have showed that the crack growth propagation is controlled by the material viscoelastic and the fracture behaviors of material, as well as the friction between the pointed blade and material. As evidenced from the fracture mechanism analysis, the friction contributes to the resistance of material against the simultaneous puncture and cutting by a factor of more than 60%. It has also been that the penetration force and the global fracture energy depend on the blade tip angle, the cutting edge angle, and the blade lubrication. Finally, an analysis of mixed‐mode fracture based on puncture/cutting by pointed blades has been described. The crack propagation is a synergistic interaction between the fracture modes I and III. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42150.